The Indian Ocean in the Eyes of a Fāṭimid Intellectual - Rümeysa Peker (Şarkiyat Mecmuası)
The Book of Curiosities (orig. Kitāb Gharā’ib al-funūn wa-mulaḥ al-ʿuyūn) is a reference work written by an anonymous author in 11th century Fāṭimid Cairo. The work consists of two volumes that examine the celestial and terrestrial worlds. The second volume focuses on the earth and is a unique geographical source with a historical context that reflects the political, social, economic, and religious perspectives of the time. The book includes many colorful maps and diagrams of the Indian Ocean, the Mediterranean and Caspian Seas, the Nile, Tigris, Euphrates, Oxus, Indus and Ganges rivers; and the major lakes of the world. The original structure of these drawings and the textual content of the work reflect how the Fāṭimids perceived the world and strategized against foreign states in the 11th century. Although the Fāṭimids are known to have developed remarkable strategies in the Mediterranean basin and to have competed for supremacy even with great states in the region such as Byzantium, the information on their activities in the Indian Ocean is quite limited. Considering the Fāṭimids’ ambitions to expand to the far East and the many struggles in which they engaged for this purpose, the Indian Ocean is also thought to have been important for this state. This study will examine how the Indian Ocean is depicted in The Book of Curiosities and in this way, will argue the Fāṭimid State to have had various ambitions in this region despite its weak direct relations and sphere of activity, and to have viewed this naval basin as a gateway to the East and a land of wonders that led to other worlds.